1996
DOI: 10.1088/0741-3335/38/12a/006
|View full text |Cite
|
Sign up to set email alerts
|

A review of the dimensionless parameter scaling studies

Abstract: The theoretical basis of the dimensionless parameter scaling technique is derived and the limitations in its application are discussed. The use of the technique is illustrated by the production on JET of a steady-state ITER similarity pulse having the same β and collisionality as the ignited ITER. The key issue of the scaling of the transport with the main dimensionless parameter ρ * is discussed in detail. Finally, possible shortcomings of the technique are examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 4 publications
4
42
0
Order By: Relevance
“…The principle of similarity assumes that physics is independent of the size scale. Accordingly, it has been demonstrated that tokamaks of different physical size but similar nondimensional parameters will have the same energy transport [23][24][25].…”
Section: The Expectation For the Fluctuation Level Versus Nondimensiomentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of similarity assumes that physics is independent of the size scale. Accordingly, it has been demonstrated that tokamaks of different physical size but similar nondimensional parameters will have the same energy transport [23][24][25].…”
Section: The Expectation For the Fluctuation Level Versus Nondimensiomentioning
confidence: 99%
“…If energy transport is dominated by plasma physics, transport coefficients, normalised to the Bohm value χ B ≡ T /eB, can be expressed as functions of three dimensionless parameters χ ≡ χ B F (ρ * , ν * , β) at fixed safety factor q, plasma geometry, and ratio T e /T i [21,22,25]; ρ * (≡ ρ i /a) is the normalized gyroradius, ν * the collisionality and β the ratio of kinetic to magnetic pressure. The confinement scaling with these parameters provide the basis for predicting the performance of the next step machines.…”
Section: The Expectation For the Fluctuation Level Versus Nondimensiomentioning
confidence: 99%
“…The difference in confinement between hydrogenic and helium-4 plasmas can also be expressed in terms of non-dimensional parameters. For a given configuration and q-profile, single ion species equipartioned plasmas dominated by high-β transport have been shown theoretically [39][40][41] to have a normalized confinement time, ω ci τ E , where ω ci is the ion Larmor frequency, which is a function of the non-dimensional plasma parameters ρ * i , β and…”
Section: Non-dimensional Parametersmentioning
confidence: 99%
“…For example in the L-mode, the beneficial effect of triangularity on density buildup is much weaker or not present, suggesting that different physics is important under these conditions. The parametrization of the density profiles is made using the dimensionless expressions ρ * , ν * and β t [12,13] used in a special definition suitable for the plasma edge. This corresponds to a collisonal high-β ansatz for the underlying transport [14].…”
Section: Introductionmentioning
confidence: 99%